Expansion of the national agriculture research and extension systems (NARES) breeding network in line with the market segmentation - CGIAR Research Program on Rice (2021)
In line with the breeding program reorganization by maturity and corresponding pipelines, the NARES partners have been identified and mapped. The regional yield trials have been sent to these partners and the partner engagement is ongoing.